A study on hydroxyapatite concentration in fibrous scaffolds and its effect on rat bone marrow stem cell proliferation / Haris Akram - Haris, Akram (2014)
Composite scaffolds of polycaprolactone (PCL) and bovine derived hydroxyapatite (HA) were produced by blending HA into PCL solution followed by electrospinning. This study mainly focused on studying the materials morphology, characteristics and interactions between the materials and cells. Six groups of scaffolds based on the weight ratio of HA in proportion to PCL were prepared (0%, 10%, 20%, 30%, 40% and 50%). The scaffolds were studied by infra-red spectroscopy (FTIR), 3D confocal laser microscopy and field emission scanning electron microscopy (FESEM) in order to determine the chemical and thermal properties as well as imaging the scaffold to cell interactions. Bone Marrow Stem Cell (BMSC) proliferation assays were carried out on Days 1, 7 and 14 using Resazurin, Deoxyribonucleic Acid (DNA) and Alkaline Phosphatase (ALP) measurements. DNA levels were used to identify cell presence and possible proliferation. ALP levels were used to indicate possible stem cell differentiation to osteoblasts. It was observed that with increasing amounts of HA in the PCL scaffold, the quantity and quality of cell attachment increased. Our study shows that the electrospun nanofibres of PCL incorporated with micro particles of HA could provide a scaffold that could be applied successfully in bone tissue engineering.